Comparison of the Abbott RealTime High Risk HPV with Genomica HPV Clinical Array for the detection of human papillomavirus DNA. Issue 11 (11th February 2013) - Sias, Catia; Garbuglia, Anna Rosa; Piselli, Pierluca; Cimaglia, Claudia; Lapa, Daniele; Nonno, Franca Del; Baiocchini, Andrea; Capobianchi, Maria Rosaria
Abstract : Human papillomavirus (HPV) has been identified as the major cause of cervical cancer worldwide and HPV DNA testing is recommended in primary cervical cancer screening. Several molecular tests for detection/typing of HPV DNA with different sensitivity and specificity are commercially available. The present study compared the performance of the Abbott RealTime High Risk HPV assay and the Genomica HPV Clinical Array CLART2 in 78 specimens (63 cervical smears and 15 rectal/urethral swabs).The typing results of the Genomica assay were in absolute agreement with each of the four possible result categories of the Abbott assay (HPV16, HPV18, Other HR HPV, not detected) in 87.2% (68/78) of the samples, with a Cohen' kappa agreement coefficient for every HR type of 0.62 (95% CI: 0.39–0.85), higher in cervical swabs (k = 0.74, 95% CI: 0.50–0.99) than in rectal/urethral swabs (k = 0.36, 95% CI: 0.00–0.82). There was an excellent agreement of the Genomica results with those of Abbott in cervical samples harbored HPV single infection (100% agreement). Nonetheless, both methods may lose sensitivity for detecting HPV types in multiple infections, giving discordant results (10/78). This underlines the importance of establishing the analytical sensitivity in HPV type detection in single and multiple HPV infections. In rectal/urethral swabs, 5 of 15 (33%) discordant cases were observed, most of which became compatible when the Genomica assay was performed starting from nucleic acid extracted with the Abbott m 2000 sp system. These results suggest that nucleic extraction based on the magnetic beads technique is suitable for HPV DNA detection in urethral/rectal swabs.